Analysis of the Effect of Perceived Usefulness, Perceived Ease of Use, and Trust of Security on Customer Loyalty through Customer Satisfaction on the OVO Application - Claudia Kenyta (Universitas Ciputra Surabaya, 2022)
Currently, mobile payment services in Indonesia are developing. One of the mobile payment services that have the most users is OVO. This research was conducted to know the effect of perceived ease of use, perceived usefulness and trust of consumers on customer satisfaction and loyalty The data in this study were obtained from distributing questionnaires to OVO users in the Surabaya area with the criteria of having used OVO for more than three months. Questionnaires were distributed to 262 respondents, and there were 202 respondents who met the criteria for further testing. The result data were processed using the CB-SEM method with SPSS and AMOS programs. The results of this study show that in the OVO application, perceived ease of use has no significant effect on perceived usefulness, perceived ease of use and perceived usefulness have no significant effect on user satisfaction, trust of security has a significant effect on customer satisfaction and customer satisfaction has a significant effect on customer loyalty